2019
DOI: 10.1080/10926771.2019.1575303
|View full text |Cite
|
Sign up to set email alerts
|

Explosive Matters: Does Venting Anger Reduce or Increase Aggression? Differences in Anger Venting Effects in Violent Offenders

Abstract: The current study aims to investigate if venting anger reduces or increases aggression. Therefore, we allowed venting anger and measured its effect on aggression after two different anger provocation paradigms in a sample of forensic psychiatric offenders (FPO, N = 45) and penitentiary offenders (PO, N = 22). These provocation paradigms included an Articulated Thoughts in Simulated Situations (ATSS) comprising anger stories, and a harassing body opponent bag (BOB) measuring punching force. To determine aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…However, the effects of anger on prison inmates appear to be not fully consistent; in a study carried out on 67 male incarcerated offenders, researchers showed how venting anger may have different effects depending on the kind of prisoner considered. Indeed, it reduces the aggression among forensic psychiatric offenders while an opposite pattern of relations was found among penitentiary offenders (Tonnaer et al, 2020).…”
Section: Angermentioning
confidence: 99%
“…However, the effects of anger on prison inmates appear to be not fully consistent; in a study carried out on 67 male incarcerated offenders, researchers showed how venting anger may have different effects depending on the kind of prisoner considered. Indeed, it reduces the aggression among forensic psychiatric offenders while an opposite pattern of relations was found among penitentiary offenders (Tonnaer et al, 2020).…”
Section: Angermentioning
confidence: 99%
“…Aggression, which is often defined as hostile, destructive, or injurious behavior, has the potential to cause serious harm to others (Hamama and Arazi 2012 ; Ho et al 2010 ; Tonnaer et al 2019 ). Youth in foster care tend to have higher levels of behavior problems, including aggression, compared to their peers in the general community (Keller et al 2001 ; Perry and Price 2017 ; Tarren-Sweeney 2008 ).…”
Section: Thought Problems and Aggression Over Time Among Youth In Foster Carementioning
confidence: 99%
“…A considerable part of the experimental research confirmed the potential harm of "emotional release" and further exposed the shortcomings of catharsis theory Tonnaer et al, 2020). According to the object of catharsis, it can be divided into "general catharsis" and "goal catharsis."…”
Section: Introductionmentioning
confidence: 95%
“…Previous theories on catharsis effectiveness mainly emphasized the role of "emotional release," believing that as long as there was "emotional release," people's anger and aggression will be reduced accordingly. In fact, if there is no "reality cognition" background, that is, the individual lacks the knowledge and evaluation of his or her environment, behavior mode and consequences, the simple emotional release is not enough to cause the individual's psychological experience to change, and may even trigger individuals' irrational negative emotions and corresponding behavior consequences Tonnaer et al, 2020;Zhan et al, 2019). The one-sided admiration of the role of "emotional release" and the erroneous neglect of the effect of "realistic cognition" have made the catharsis theory severely criticized by researchers holding social learning theory and other views for a long time.…”
Section: Introductionmentioning
confidence: 99%